2020
DOI: 10.1111/acfi.12707
|View full text |Cite
|
Sign up to set email alerts
|

Do females on boards affect acquisition outcomes and target selection: a replication and extension of Levi, Li and Zhang (2014)

Abstract: We replicate and extend the 2014 study by Levi, Li and Zhang in the Australian setting and examine whether female representation on corporate boards affects acquisition outcomes. Consistent with the original study, we find that bidders with female representation on their boards make fewer acquisitions and pay lower premiums, on average. We also document that bidders with female representation on their boards prefer to select target firms that also have female representation on their boards. These results are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…We felt it relevant to replicate this study in the Australian setting given the increasing pressure on Australian listed firms to increase female representation on boards (KPMG, 2020). Having successfully replicated Levi et al (2014) and extending the original sample period by 10 years, our we confirmed that the observed phenomena are invariant to the institutional setting and temporal aspect (Bachmann and Spiropoulos, 2020). Hence, females on boards appear to improve corporate outcomes in the absence of gender quotas, at least in the setting of acquisitions.…”
Section: Introductionsupporting
confidence: 71%
“…We felt it relevant to replicate this study in the Australian setting given the increasing pressure on Australian listed firms to increase female representation on boards (KPMG, 2020). Having successfully replicated Levi et al (2014) and extending the original sample period by 10 years, our we confirmed that the observed phenomena are invariant to the institutional setting and temporal aspect (Bachmann and Spiropoulos, 2020). Hence, females on boards appear to improve corporate outcomes in the absence of gender quotas, at least in the setting of acquisitions.…”
Section: Introductionsupporting
confidence: 71%
“…Overall, these findings support how women are more cautious and conservative in decision-making than their male counterparts, and these characteristics might determine female risk tolerance (Bachmann & Spiropoulos, 2020;Levi et al, 2014).…”
Section: Introductionsupporting
confidence: 54%
“…Several studies examined the role of different types of board demography in different external change types (Bachmann & Spiropoulos, 2021; Clout et al., 2021). Furthermore, a large body of research examined the role of different board human and social capital in acquisitions (e.g., Greve & Zhang, 2017; Güner et al., 2008; Hilscher & Şişli‐Ciamarra, 2013; Masulis & Mobbs, 2011; McDonald et al., 2008).…”
Section: Board Governance Of Different Strategic Change Typesmentioning
confidence: 99%